A Construction Method of Power Grid Monitoring Knowledge Graph. Issue 1 (1st January 2022) - Liu, Yi; Huang, Xinjian; Li, Sen; Gao, Shang; Ji, Kun; Li, Huihui; Xu, Hanyang
Abstract: Centralized monitoring and integrated intelligent alarm functions have been implemented on the control system of smart power grid, which provides technical support for the judgment and disposal of power grid accident. However, there are still some problems such as lack of systematic analysis tools and cannot realize the correlation of alarms. This paper proposes a power grid accident analysis method based on monitoring information knowledge graph, which is constructed with power grid topology and historical alarm data rules. Using this method, the staff can accurately and quickly judge the power grid accident with the support of grid topology and alarm correlation, so as to improve the efficiency of power grid accident analysis and reliability of power grid control system.